2011
DOI: 10.5271/sjweh.3139
|View full text |Cite
|
Sign up to set email alerts
|

3rd place, PREMUS best paper competition: development of the return-to-work self-efficacy (RTWSE-19) questionnaire – psychometric properties and predictive validity

Abstract: The following articles refer to this text: 2011;37(2): 81-168; 2016;42(4):257-353

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 51 publications
6
101
1
14
Order By: Relevance
“…In the 19-item version, the internal consistency of total self-efficacy score was 0.96 (10). Total mean scores are calculated and the higher the score, the higher the self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 19-item version, the internal consistency of total self-efficacy score was 0.96 (10). Total mean scores are calculated and the higher the score, the higher the self-efficacy.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy plays a key role in decisions and behaviors concerning job and career development (6,7) and it has proven to be predictive of future work participation and RTW after being on long-term sickness absence (4,5,(8)(9)(10)(11). In a prospective study, Fitzgerald et al (12) found self-efficacy to be a strong predictor of RTW one month after coronary artery bypass grafting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En relación con el tipo de muestra se percibe que las mayores frecuencias eran de trabajadores, sin especificación del tipo de organización en que ellos ejecutaban sus funciones laborales (Cinamon, 2006;Federici & Skaalvik, 2011;Hennessy & Lent, 2008;King, 2009;Salanova et al, 2011;Strauser et al, 2010;Waghorn, Chant & King, 2007), seguido de estudios que contaron con muestras de personas que estaban retornando al trabajo después de ser alejados por problemas de enfermedad o accidentes de trabajo (Bains et al, 2012;Brouwer et al, 2011;Lagervelda, Blonka, Brenninkmeijerb & Schaufelib, 2010;Shaw, Reme, Linton & Pransky, 2011;Soeker, 2012). En menor frecuencia se encontraron estudios que investigaron estudiantes que trabajaban (Cinamon, 2010;Pepe, Farnese, Avalone, & Vecchione, 2010;Riggio & Desrochers, 2006), trabajadores de empresas públicas (O'Sullivan et al, 2012;Vax, Schreuer & Sachs, 2012), provenientes de empresas públicas y privadas (Chaudhary, Rangnekar & Barua, 2012;Gismero-González et al, 2012), trabajadores de empresas privadas (Panatika, O'Driscollb & Anderson, 2011), así como muestra de trabajadores voluntarios y temporarios (Ferrari, 2004).…”
Section: Discussionunclassified
“…La primera publicación que utilizó el instrumento es de 2005, y en relación con los parámetros psicométricos presenta estudios de validez con base en la estructura interna, con base en la relación con otras variables y estudios de precisión del tipo test-retest y consistencia interna (Besen, Young, & Shaw, 2015;Huijs, Koppes, Taris & Blonk, 2012;Lagervelda et al, 2010;Shaw et al, 2011).…”
Section: Discussionunclassified